88.0k views
0 votes
Need this by tonight

Need this by tonight-example-1
User Pega Wega
by
6.4k points

1 Answer

6 votes

Answer:


f(-1)=(-1)/(2)


g(-2)=(5)/(32)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction

Explanation:

Step 1: Define


f(x)=(2x-1)/(2x^3-8x)


g(x)=(2x-1)/(2x^3+8x)

f(-1) is x = -1

g(-2) is x = -2

Step 2: Evalaute

f(-1)

  1. Substitute:
    f(-1)=(2(-1)-1)/(2(-1)^3-8(-1))
  2. Evaluate:
    f(-1)=(2(-1)-1)/(2(-1)-8(-1))
  3. Multiply:
    f(-1)=(-2-1)/(-2+8)
  4. Subtract/Add:
    f(-1)=(-3)/(6)
  5. Divide:
    f(-1)=(-1)/(2)

g(-2)

  1. Substitute:
    g(-2)=(2(-2)-1)/(2(-2)^3+8(-2))
  2. Evaluate:
    g(-2)=(2(-2)-1)/(2(-8)+8(-2))
  3. Multiply:
    g(-2)=(-4-1)/(-16-16)
  4. Subtract:
    g(-2)=(-5)/(-32)
  5. Simplify:
    g(-2)=(5)/(32)

And we have our final answers!

User JAYBEkster
by
5.8k points